Constituent Recall bagi Anggota Dewan Perwakilan Daerah (DPD) RI - Muhammad RM Fayasy Failaq; Rohmatin Dwi Arti; Audina El-Rahma; Rizki Maulana Syafei (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2023)
DPD institution has many problems. On the other hand, the recall mechanism (PAW) as a forum that guarantees DPD accountability to the constituents is also problematic. It has been proven, in practice since 2014, recalls in the DPD have not been carried out as effectively as in the DPR. Recall arrangements which are mandated by the constitution through Act of Legislative produce two main focuses of this research in the form of dissecting problems and providing recommendations for arrangements whose output is reforming laws. This research method is normative juridical with qualitative data analysis from legal materials related to the theme. This study concludes that the problem of recall in the DPD is in the form of a mechanism that is less participatory for local communities as well as potential conflicts of interest because it is resolved dominantly internally by the DPD leadership and BK (Honorary Board) of the DPD. Then, the ideal recall for the DPD is a constituent recall with the Regional Government (Governor and Provincial DPRD) which proposes an interim termination on the basis of the argumentation of the reciprocal relationship between the two on the aspect of regional autonomy. In order not to be co-opted, the regional government is obliged to make the aspirations of the people the main substance of the recall. In addition, decisions can be more objective and careful because there is a relationship of checks and balances between the Governor and the Provincial DPRD.